Socio-demographic factors of patients who underwent free cataract surgery in Kafanchan, Nigeria - Sano, Ulus Stanley; Sarki, Pamela Diyale (International Journal Of Community Medicine And Public Health, 2021)
Background: The aim of this study is to determine the socio-demographic profile of people accessing cataract surgery at a free cataract surgical Camp in Kafanchan. Methods: One hundred and nine participants had manual small cataract incision surgery with intraocular lens over a three-month period (September to November 2018) and were followed up for two months. Visual acuity was assessed at first day and two months post-op along with refraction and best corrected visual acuity. Their socio-demographic features along with duration of lost vision and cause of delay in cataract surgery were also noted. Results: Fifty-five males and fifty- four females had cataract surgery and were followed up for two months post-op. Fifty (45.9%) had no formal education while fifty-nine (54.1%) had formal education. Among those with formal education 59% (34) were males while 41% (20) were females. Majority of participants earned less than two hundred and fifty thousand naira (six hundred and twenty-five US dollars) annually. Eighty-two (75%) of participants were Christians and 71 (65%) lived in rural areas. Sixty-five (60%) had lost vision in the index eye more than one year prior to presentation for surgery and the main reason in this study for delay in having cataract surgery was immaturity of the cataract. Conclusions: Some socio-demographic factors are barriers to cataract surgery.